PLATFORMS AS A BUSINESS MODEL: GAINING A COMPETITIVE ADVANTAGE THROUGH AN ECOSYSTEM APPROACH - SMETANIUK, Olena; TSISAR, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The object of the article’s research is platforms as a business model and their role in achieving competitive advantage using an ecosystem approach. The topicality of the researched problem lies in the perspective of enterprises using the platform to ensure increased efficiency, innovation and cost of products. As a result of the analysis, it was established that platforms contribute to the transformation of traditional business models, providing a convenient infrastructure for interaction between various participants. This allows companies to create an ecosystem where each member brings their knowledge, resources and products that together create value for customers. An ecosystem approach allows businesses to focus efforts on developing their core competencies, share risks, and reduce costs by sharing resources. The obtained results are explained by the fact that the modern business environment requires a more flexible and innovative approach to ensuring competitiveness. Platforms allow enterprises to be more adaptable to changes in market conditions, to respond to new opportunities and challenges, and to attract external partners for joint growth. These results can be used in practice by enterprises of various industries. The integration of the platform approach allows you to create a favorable environment for innovation, the development of new products and services, as well as to ensure sustainable growth thanks to joint interaction with various ecosystem players. The article substantiates the importance of the ecosystem approach in using platforms as a business model to ensure competitive advantage. The results of the study confirm that platforms can become a key tool for enterprises seeking innovative growth and defining new standards in their industries. Platforms as a business model are indeed a powerful tool for achieving competitive advantage through an ecosystem approach. The results of this study indicate that in modern business it is important not only to compete, but also to cooperate, ensuring mutual benefit for all participants of the ecosystem.